Understanding the legal regulation of suicide incitement in the contemporary criminal law with a case study on Bosnia and Herzegovina - Softić, Lejla; Çakar, Ena Kazić (DIXI, 2025)
Incitement to suicide has been regulated differently in the majority of legal systems worldwide, through both direct codification and as a part of other criminal offenses. The modern media of communication that had been developed brought new legal challenges in preventing harmful impacts from one person to another, which may result in suicide. Very recently, similar cases took place in Bosnia and Herzegovina, leaving many questions unresolved: should the individuals who were (online) mocking the victim be treated as inciters, thus criminal offenders? Therefore, unveiling the legal regulation of acts of criminal offense Incitement to Suicide tests if the legislation updated their norms in line with these new challenges. Through doctrinal and comparative methods, a legal analysis of the regulation of incitement to suicide will be conducted in this manuscript, withstanding factual differences in its’ sanctions and difficulties in prosecution, with the focus being on the criminal law of Bosnia and Herzegovina. Comparison will be made with the regulations in the United States, United Kingdom, Netherlands, and Germany. The manuscript will result in recommendations about the prevention of critical events and incitement to suicide to be perpetrated.